Assessment of Job Stress among Nurses Working in Akre Teaching Hospitals - Mohanned Khaleel Abdullah; Zikri Mahmood Mirza; Shevan Younis Othman (College of Nursing,University of Mosul, 2018)
Background and Aim: The phenomenon of Job Stress remains a reality that touches on different areas of work with inequality. Sources and levels of pressure from one field to another, particularly affecting the humanitarian field as it has proved. Many studies compare careers, under the study of job stress in particular the fields of teaching and nursing as they involve a number of tasks and responsibilities relationships.The study aimed to identify the relationship between job stress and nurses' demographical characteristics. Materials and Method: Aquantives descriptive study was applied study to determine job stress for nurses in Akre teaching hospitals in Dohuk city. About 75 nurses participants from two hospitals, Gulan General Teaching Hospital and from Akre General Emergency Teaching Hospital were chosen randomly. A questionnaire is constructed by researchers is divided into two sections, the 1st section is the demographical characteristics of nurses and the 2nd section consists of 23 items about job stress. Results: The study shows that high percentage of the study population where less than 30 years old and most of them married and male the findings show that 61.3% of nurses where graduated from medical instituted. the study revealed that 61.3% of the sample had less than seven years of experience. The finding displayed that there is a significant difference between job stress among nurs's age, years experience, Position, Marital status and Salary, While there is no significant difference in relation to Education levels ,Setting, Gender and Hospital.. Conclusion: The results revealed that the young, single and new employed with low salaries nurses suffer from job stress more than the older, married, wide experienced senior nurses. And all the sample have follow almost the same curriculum and instructions to deal with stress in the hospitals. Recommendations: The researchers reommnded for improving the working conditions of workers in sectors of a humanitarian nature, including a sector education and nursing sector so that their employees can provide better services . Key wards: job stress, Akre hospital, assessment, nurses.